The relation between avian coronaviruses and SARS-CoV-2 coronavirus - Al-Khalaifah, Hanan; Alotaibi, Mohammad; Al-Nasser, Afaf (Frontiers in Microbiology, 2022)
The coronaviruses are a family of ribonucleic acid viruses that are present in both mammals and birds. SARS-CoV and MERS-CoV originated in bats, and there is a possibility that this could be the case for SARS-CoV-2 as well. There is already evidence that a probable intermediary host is responsible for the emergence of viruses in humans as was the case for SARS-CoVs and MERS-CoV. As the SARS-CoV-2 originated from a live animal market, there is always the question if domestic animals are susceptible to these viruses and the possible risk of zoonotic transmission with mammals, including humans. This uncertainty of the transmission of COVID-19 virus between human and animals is of great significance worldwide. Hence, this paper focuses on the avian coronaviruses and their possible relation and interaction with SARS-CoV-2.